2017
DOI: 10.1177/1049909117740848
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Compassion Satisfaction in Clinicians: A Pilot Intervention Study for Reducing Compassion Fatigue

Abstract: While the small sample size of this pilot study limits the generalizability of the findings, there were positive effects for CS and BO in participants over time, indicating possible benefits of providing self-care education to healthcare providers. Additional research with a larger sample size is needed to address how healthcare providers might further benefit from resiliency education and interventions to improve professional quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 38 publications
(68 reference statements)
0
57
0
1
Order By: Relevance
“…Although the patient groups receiving the PGx educational intervention were small in this pilot study, the ~ 20% improvements in knowledge about PGx are on par with other similar educational interventions outside of the realm of genomics . Interestingly, after accessing the patient portal, almost all patients (90%) would share their results with their healthcare providers and 60% would share their results with pharmacists.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Although the patient groups receiving the PGx educational intervention were small in this pilot study, the ~ 20% improvements in knowledge about PGx are on par with other similar educational interventions outside of the realm of genomics . Interestingly, after accessing the patient portal, almost all patients (90%) would share their results with their healthcare providers and 60% would share their results with pharmacists.…”
Section: Discussionmentioning
confidence: 87%
“…We prespecified a target sample size of 10–12 participants per group for the 2 separate days of testing (anticipating that there would be dropout among those who agreed by telephone before the actual participation day). This planned sample size was in accordance with other literature, which demonstrated that detectable increases in knowledge and changes in perceptions were measurable in pilot groups of this size . We contacted patients by telephone for potential participation in one of two study sessions: one group consisted of patients who had previously received broad pre‐emptive genomic testing and whose actual results had been previously made available to their treating physicians (PGx), and a second control group consisted of patients who had not received genomic testing within the context of “The 1200 Patients Project,” reflecting traditional care (TC).…”
Section: Methodsmentioning
confidence: 91%
See 2 more Smart Citations
“…Often seen as a dual-edged problem, work stress impacts not only the individual but also the organization in terms of lost productivity, absenteeism, and health-related costs (Yuwanich, Sandmark, & Akhavan, 2016). The lexicon and science that have now developed in conjunction with work stress encompass burnout, depression, compassion fatigue, engagement, emotional intelligence, resilience, as well as job satisfaction and job turnover (Bianchi, Mayor, Schonfeld, & Laurent, 2018; Klein, Riggenbach-Hays, Sollenberger, Harney, & McGarvey, 2018; Väänänen et al, 2012). Various researchers have examined these characteristics of individuals in relation to work-contextualized factors, such as autonomy, job demands and/or job resources, social support, and supervision (Bakker, Demerouti, & Euwema, 2005; Frone, Russell, & Cooper, 1995; Leiter, Gascón, & Martinez-Jarreta, 2010; Shanafelt et al, 2015).…”
mentioning
confidence: 99%